Gastroduodenal Lesions in Racehorses: Evaluation and Mapping According to the Updated Sidney System and Equine Gastric Ulcer Syndrome Council Classification - Leite, Juliana da Silva; Cury, Leopoldo José; Ferreira, Ana Maria Reis (Brazilian Journal of Veterinary Pathology, 2012)
Gastroduodenal ulceration is found in 90% of Thoroughbred race horses. The clinical and economical importance of gastric ulcers and the scarce information about the subject in Brazil make this investigation essential. The aim of this study was to evaluate and map grossly and microscopically the gastroduodenal lesions in race horses according to the Updated Sidney System and the Equine Gastric Ulcer Syndrome Council (EGUSC) Classification. Necropsy was performed in 14 horses and macroscopy was described. Samples of the gastric regions (14 animals - nonglandular fundus, glandular fundus, margo plicatus, antrum and pylorus) and duodenum (9 animals) were obtained and processed for routine histopathology. Macroscopic evaluation of the lesions based on the Updated Sidney System showed that 100% of the horses had gastric ulcers or erosions, mainly located at the margo plicatus. The Updated Sidney System also allowed a macroscopic gastritis classification and revealed that seven horses had enanthematous gastritis (50%), four had hemorrhagic gastritis (28, 6%), and three had erosive gastritis (21, 4%). Based on the EGUSC Classification, the most frequent score is 2 (50%). The score 3 was found in 35,7% of the horses and the scores 1 and 4 in 7,1% each. The score 0 which means intact epithelium, was not seen in any of the horses. Histopathological evaluation based on the Updated Sidney System revealed mild to severe lymphoplasmacytic infiltrate, sometimes with areas of neutrophilic infiltrate, demonstrating some activity mainly in the injured mucosa. Lymphoid follicles were found in 92.9% of the animals. This study confirms that gastric ulceration in Brazilian race horses is common, and the majority consists of chronic ulceration of the margo plicatus. The use of the histopathological division of the Updated Sidney System demonstrated that chronic gastritis was predominant and the majority of cells in the inflammatory infiltrate were lymphocytes and plasmocytes. This study also showed that the association of the Updated Sidney System and the EGUSC Classification is feasible and leads to a better understanding of equine gastroduodenal ulceration. Although usually neglected, these lesions may be involved in low performance rates and therefore other investigations are necessary for the elucidation of the etiology and pathogenesis of these ulcers.